2020
DOI: 10.1007/s10021-020-00519-2
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Biogeomorphic Seagrass Landscapes for Coastal Protection: Persistence and Wave Attenuation During Major Storms Events

Abstract: The intensity of major storm events generated within the Atlantic Basin is projected to rise with the warming of the oceans, which is likely to exacerbate coastal erosion. Nature-based flood defence has been proposed as a sustainable and effective solution to protect coastlines. However, the ability of natural ecosystems to withstand major storms like tropical hurricanes has yet to be thoroughly tested. Seagrass meadows both stabilise sediment and attenuate waves, providing effective coastal protection service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Further to this point, we also realize that the time periods covered by the integration of remote sensing estimates could result in changes in seagrass position or density, which may underline some of the differences between estimates derived using remote sensing images acquired in different years. However, Caribbean seagrass ecosystems are tolerant of hurricanes and the extensive carbonate bank habitat where they reside functions to dissipate and distribute wave energy from storms 31 . As a result, surveys have suggested that seagrasses in The Bahamas are relatively stable, seeing negligible changes in the last 10–20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Further to this point, we also realize that the time periods covered by the integration of remote sensing estimates could result in changes in seagrass position or density, which may underline some of the differences between estimates derived using remote sensing images acquired in different years. However, Caribbean seagrass ecosystems are tolerant of hurricanes and the extensive carbonate bank habitat where they reside functions to dissipate and distribute wave energy from storms 31 . As a result, surveys have suggested that seagrasses in The Bahamas are relatively stable, seeing negligible changes in the last 10–20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Coral reefs sheltering tropical bays and lagoons provide favorable conditions for the growth of seagrass. Seagrass meadows minimize erosion of sandy beaches by stabilizing the sediment and dissipating waves both during calm and hurricane conditions (James et al, 2019(James et al, , 2020. Healthy vegetated foreshore ecosystems, therefore, play an important role in mitigating coastal flooding caused by natural hazards and increases the resistance of coastal areas to storm surges.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Accordingly, the similitude of the inertia, the gravitation, and the viscosity forces, between the real and the model could still be retained (Zeller et al, 2014). Likewise, the characteristics of seagrasses are essential for predicting the wave dissipation parameter in numerical models (van Rooijen et al, 2016b;James et al, 2021;Yin et al, 2021). However, the literature related to Indonesian seagrasses remains limited or non-existence.…”
Section: The Identification Of Indonesian Seagrass Physical Character...mentioning
confidence: 99%